Isolation and Characterization of Lignin from Tropical and Temperate Hardwood (Bangladesh Journal of Scientific and Industrial Research, 2010)
Dioxane and milled wood lignins (MWL) were isolated from tropical hardwood, Nalita (Trema orientalis) and temperate hardwood, aspen. These lignins were characterized by UV, FTIR, 1H-NMR and 13C-NMR spectroscopy, alkaline nitrobenzene oxidation, molecular weight determination, elemental and methoxyl analysis. The structural analysis revealed that Nalita and aspen lignin is syringyl-guaiacyl type. Aspen lignin had higher syringyl unit than Nalita lignin. The β-O-4 type linkages are the main interunit linkages and more abundant in aspen than Nalita. Dioxane lignin showed higher free phenolic hydroxyl group than MWL in both species. The weight average molecular weight of aspen lignin was lower than that of Nalita lignin. Nalita and aspen lignins contained both erythro and threo configuration, but erythro proton gave stronger peak. A UV absorption maximum of aspen lignin was at 274 nm, whereas it was shifted to 280 nm for Nalita lignin. Keywords: Trema orientalis, Aspen, Dioxane lignin, Milled wood lignin, Syringyl-guaiacyl, β-O-4 linkages DOI: 10.3329/bjsir.v44i3.4399 Bangladesh J. Sci. Ind. Res. 44(3), 271-280, 2009